Penerapan System Usability Scale dalam Pengukuran Kebergunaan Website SMKN 13 Bandung - Akbar, Imannudin (INTERNAL (Information System Journal), 2024)
SMKN 13 Bandung is a vocational school that prioritizes information technology, most interactions and activities utilize information technology in order to achieve the school's vision and mission. Based on observations and problems found on the SMKN 13 Bandung website, there has been no attempt to evaluate measurements of user usability and satisfaction when visiting this website. This is to ensure that the SMKN 13 Bandung website in the future can be developed and operated with optimal quality according to the experience and needs of its users. In measuring usability, this research uses the System Usability Scale (SUS) method. This is because SUS is a valid and reliable tool for testing usability even on small samples. The SUS score results obtained from measurements on the SMKN 13 Bandung website resulted in an average SUS score of 71.29. These results show that the SMKN 13 Bandung website is quite usable, acceptable but still needs to be evaluated and developed to a better stage. The results of the measurements carried out can be the first step for evaluating the SMKN 13 Bandung’s website.